Osmoregulation in symbiosis-independent mutants of Bdellovibrio bacteriovorus. - Varon, M (1977)
Bdellovibrios capable of axenic growth grow in a cell-free medium at a rate considerably lower than that attainable in a two-membered culture with Escherichia coli. The axenic growth rate may be improved either by adjustment of the osmosity of the medium or by the addition of low concentrations of spermine.